Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000314764
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Strength and Lung Function in Patients Undergoing Medical Thoracoscopy

Abstract: Background: Medical thoracoscopy (MT) is a procedure considered as minimally invasive. The safety of the procedure has been questioned recently in fragile patients, but no explanation of the pathophysiologic mechanism has been given. Although MT is applied by respiratory physicians who are also dealing with patients with impairment of lung function, it is surprising that there are no data concerning lung mechanics and function in this patient population. Objectives: To assess respiratory muscle strength and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(64 reference statements)
0
13
0
1
Order By: Relevance
“…Thoracoscopy is associated with a transient impairment in lung function, which is more pronounced when pleurodesis is performed [46]. With the exception of some complications related to the technique itself [47], which could be prevented using ultrasound examination, the most relevant are systemic complications associated with intrapleural instillation of the sclerosant.…”
Section: Mechanisms Associated With Complications Of Pleurodesismentioning
confidence: 99%
“…Thoracoscopy is associated with a transient impairment in lung function, which is more pronounced when pleurodesis is performed [46]. With the exception of some complications related to the technique itself [47], which could be prevented using ultrasound examination, the most relevant are systemic complications associated with intrapleural instillation of the sclerosant.…”
Section: Mechanisms Associated With Complications Of Pleurodesismentioning
confidence: 99%
“…The interpretation we postulate to hold true is the following: group B had a large effusion volume compressing a large part of ipsilateral lung having remained atelectatic for a certain time period. When decompressed after fluid removal (T2), the dysfunctional surfactant due to previous atelectasis resulted in an elevation of the diaphragm and alteration of its length-tension property, thus generating lower MIPs 34 35 Froudarakis et al ,36 who had studied patients undergoing medical thoracoscopy for large pleural effusions, had also found decreased MIP the day after the procedure, which was gradually restored during the following days.…”
Section: Discussionmentioning
confidence: 99%
“…There might be other clinical and research applications of pleural pressure measurement. For example, Froudarakis et al [18 ]have recently shown that respiratory muscle strength and lung function can be temporarily impaired after medical thoracoscopy. According to our studies, pleural pressure measurements before and after the procedure may add new information on the mechanisms of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%